Giraffes Can't Dance - Andreae, Giles 1966-; Parker-Rees, Guy (New York : Orchard Books, 2001)
Gerald the giraffe is too clumsy to dance with all the other animals at the Jungle Dance, until he finds the right music.
Accelerated Reader AR